Enhancement of charge transport of a dye-sensitized solar cell utilizing tio2 quantum dot photoelectrode film - Zaine, S.N.A. (MDPI, 2021)
A dye-sensitized solar cell (DSC) is the third generation of solar technology, utilizing TiO2 nanoparticles with sizes of 20â30 nm as the photoelectrode material. The integration of smaller nanoparticles has the advantage of providing a larger surface area, yet the presence of grain boundaries is inevitable, resulting in a higher probability of electron trapping. This study reports on the improvement of charge transport through the integration of quantum dot (QD) TiO2 with a size of less than 10 nm as the dye absorption photoelectrode layer. The QD TiO2 samples were synthesized through solâgel and reflux methods in a controlled pH solution without surfactants. The synthesized samples were analyzed using microscopic, diffraction, absorption, as well as spectroscopic analyses. A currentâvoltage and impedance analysis was used to evaluate the performance of a DSC integrated with synthesized TiO2 as the photoelectrode material. The sample with smaller crystallite structures led to a large surface area and exhibited a higher dye absorption capability. Interestingly, a DSC integrated with QD TiO2 showed a higher steady-state electron density and a lower electron recombination rate. The shallow distribution of the trap state led to an improvement of the electron trapping/de-trapping process between the Fermi level and the conduction band of oxide photoelectrode material, hence improving the lifetime of generated electrons and the overall performance of the DSC. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).